Anna Seldbritt at the National Museum of Fine Arts in Buenos Aires: A New Interpretative Proposal - Montemurro, María Laura (Eikón / Imago, 2015)
Amidst the ancient and medieval sculptures preserved at the National Museum of Fine Arts in Buenos Aires, there is a 15th. Century German wood carving of St. Anne with the Virgin Mary and the Child. This iconography, known in Germany as Anna Selbdritt, achieved a great measure of popularity in Northern Europe during the last years of the Middle Ages. The prevailing interpretation of this iconographic type regards Mary and the Child as attributes of St. Anne. However, the peculiarities of the rendering of Anne and Mary in this, and other, similar carvings, open in our view a series of issues for consideration. Departing from these observations, this paper proposes a new interpretation, mainly supported in the rather youthful image of St. Anne, as well as in some ambiguities in that of Mary.